Privacy Protection in Cloud Computing. - Medaboina, Lakshmi; Mohammed, Moulana (Turkish Journal of Physiotherapy Rehabilitation, 2021)
Cloud computing is appearing like a prevalent data interactive paradigm to appreciate users data remotely stored in an internetcloud server. Cloud services supplybetterbenifits for the users to like the on-request cloud applications without thinking about the neighborhood foundation impediments. During the information getting to, different users areadditionally in a very collaborative relationship, and thus information sharing gets huge torealize productive benefits. The previous security methodsmainly concentrateon theauthentication tounderstandthatauser'sprivativedata cannotbe unauthoriz edaccessed, butneglect a inconspicuous protection issue during a client moving the cloud worker to look for different clients for information sharing. The tested admittance demand itself may uncover the user's privacy despite whetheror not it can obtain the information access permissions. Previous System does not have the option of granting/revoking data access. In this paper, we proposedthe safedevice and informationholder can decide the user can use the system or not.